Knowledge retention and age management – senior employees’ experiences in a Swedish multinational company - Wikström, Ewa; Eriksson, Ellinor; Karamehmedovic, Lejla; Liff, Roy (Journal of knowledge management, 2018)
Purpose The focus of this study is on the knowledge retention process, including knowledge capture, knowledge codification and the internalising of knowledge in organisations – a key aspect of age management. The purpose of this paper is to contribute to an understanding of the difficulties in this process to discuss implications for organizational measures to retain knowledge. Design/methodology/approach This study is based on field research on a Swedish multinational company from the perspective of senior employees. Findings The findings indicate that knowledge retention is a complex phenomenon, partly because valued knowledge is tacit and knowing is highly subjective and transferred through learning in collaboration with others in the process of undertaking assignments and acting together in work situations. Research limitations/implications Knowledge retention is considered only from the perspective of senior, white-collar employees in this study; it would be of interest to consider other employees’ perspectives as well. A second limitation is that the data were collected at a single site. It could be argued, however, that a single case study research format provides an opportunity to gain deep knowledge and allows for explanations about observed phenomena, thereby contributing towards transferable scientific knowledge. Practical implications Knowledge retention is hindered by focusing solely on senior workers and on an explicit and commodified view of knowledge. Social implications Knowledge retention should be an on-going way of working throughout the organization in which tacit knowledge and knowing are important. Originality/value This study shows the importance of considering knowledge and knowing retention as a matter of continual interaction between actors. Retention of tacit knowledge and knowing is not merely a matter of capturing and codifying knowledge. This study contributes to an understanding of the internalisation of tacit knowledge and knowing in continual interaction and cannot be preceded by a step-wise process.